Answer:
[tex]h_g=-g^2+7g+1\\\\h_1=7\\\\h_2=11\\\\h_3=13\\\\h_4=13[/tex]
Step-by-step explanation:
Given the rate of filling is [tex]5g^2+3g-2[/tex] and the rate of emptying the pool is [tex]6g^2-4g-3[/tex]. The height of the pool at any time is:
[tex]h_t=R_{in}-R_{out}, h_t- \ height \ at\ time\ t\\\\h_t=(5g^2+3g-2)-(6g^2-4g-3)\\\\h_t=-g^2+7g+1[/tex]
#Substitute the value of g in the height equation to find the height of the pool:
#g=1
[tex]h_t=-g^2+7g+1, \ g=1\\\\h_t=-(1)^2+7(1)+1\\\\=7[/tex]
#g=2
[tex]h_t=-g^2+7g+1, \ g=1\\\\h_t=-(2)^2+7(2)+1\\\\=11[/tex]
#g=3
[tex]h_t=-g^2+7g+1, \ g=1\\\\h_t=-(3)^2+7(3)+1\\\\=13[/tex]
#g=4
[tex]h_t=-g^2+7g+1, \ g=1\\\\h_t=-(4)^2+7(4)+1\\\\=13[/tex]